Conceptual design of products from natural fibre composites - Salit, Mohd Sapuan (2014)
This paper presents review of various conceptual design methods in the development of products from natural fibre composites. The products reported include small boat, automotive parking brake lever, automotive bumper beam, chair, multipurpose table, trolley base, telephone stand, book shelf, and computer casing. Two major activities in conceptual design agate, i.e. concept generation and concept evaluation were discussed.